Hubungan antara Dukungan Sosial Teman Sebaya dengan Motivasi Akademik Mahasiswa Tingkat Akhir dalam Menyelesaikan Skripsi di Universitas Negeri Padang - Rahmadani, Irma Novita; Nio, Suci Rahma (Lembaga Yasin AlSys, 2025)
Thesis writing is a complex process that often presents various challenges for final-year students. One of the main obstacles encountered is low motivation, which leads to delays in completing final assignments and graduation. Academic motivation plays a crucial role in encouraging students to complete their studies on time. One external factor believed to enhance academic motivation is peer social support. This study aims to examine the relationship between peer social support and academic motivation among final-year students completing their thesis at Universitas Negeri Padang. The research employed a quantitative method with a correlational approach. The sample consisted of 100 respondents selected through proportionate stratified random sampling. The research instruments included a peer social support scale and an academic motivation scale, with data analyzed using Pearson correlation. The results show a significant positive relationship between peer social support and academic motivation, with a correlation coefficient of 0.316 and a significance level of 0.001 (p < 0.05). These findings indicate that the higher the peer social support, the higher the academic motivation of students in completing their thesis.